Partnering with poetry: poetry in American education standards from 1971-2010 - Van Zant, Melissa G. (Kansas State University, 2017)
American education is increasingly driven by standards and high-stakes tests. This creates a dynamic in which curricular content addressed in the standards will be subjected to high-stakes tests while that not addressed in the standards risks being ignored. Such a dynamic threatens poetry—a subject whose strength resides in its ambiguity instead of one correct answer. The literature review establishes poetry as an important area of study for K-12 students and explores how the Standards Movement has affected poetry instruction in other English-speaking countries. This research used context-sensitive textual analysis to examine the treatment of poetry in American English language arts standards from 1971 to 2010 as demonstrated in the following three documents: (1) Representative Performance Objectives for High School English written by the Tri-University Project in 1971, (2) Standards for the English Language Arts written by the National Council of Teachers of English and the International Reading Association in 1996, and (3) the Common Core State Standards for English Language Arts written in 2010. Context-sensitive textual analysis (Huckin, 1992) presumes that the contexts in which texts are written and read impact their meanings. The study describes those impacts, their implications, and suggestions for continued study.
Keywords: Poetry; Education; Standards; English; K-12; Context-sensitive text analysis